Increasing efficiency of multiple listing service systems applying web‐based decision support system for real estate - Kaklauskas, Artūras; Gikys, Mindaugas (Journal of Civil Engineering and Management, 2005)
One of the major problems in Multiple Listing Service Systems is to find what you want. Number of real estate alternatives on the Internet is thousands. How can customers find the rational alternative on the Internet? Once real estate is found, the customer usually wants to compare alternatives. There are five types of aids to comparison shopping: search on hypertext files by agents, search alternatives on databases, alternative search and tabular comparison, comparison of alternative products and services from multiple malls, search and multiple criteria decision‐making. Therefore, the efficiency of Multiple Listing Service Systems may be increased by applying multiple criteria decision support systems developed by authors. The authors have developed Web‐based Decision Support System for Real Estate (DSS‐RE). Proposed DSS‐RE can create value in next important ways: help customers assess their needs, identify suitable real estate to fulfil needs, compare and evaluate real estate, help customers evaluate the usefulness of the real estate in the after‐purchase evaluation stage, etc.Naudojimosi nekilnojamojo turto agentų duomenų bazėmis efektyvumo didinimas taikant internetinę nekilnojamojo turto sprendimų paramos sistemąSantraukaAutoriai atliko pasaulyje naudojamų nekilnojamojo turto agentų duomenų bazių apibrėžimų apžvalgą ir išnagrinėjo Lenkijoje ir Rusijoje sukurtas nekilnojamojo turto agentų duomenų bazes. Remiantis šių duomenų bazių analizė, siekiant padidinti naudojimosi jomis efektyvumą, sukurta internetinė nekilnojamojo turto vertinimo daugiakriterinė sistema. Internetinėje nekilnojamojo turto vertinimo daugiakriterinėje sistemoje realizuota daugiakriterinė alternatyvų analizės sistema, leidžianti vartotojui išsirinktus nekilnojamojo turto objektus lyginti remiantis kiekybiniais ir kokybiniais kriterijais. Sistema atlieka alternatyvų paiešką bei daugiakriterinę analizę nustatant alternatyvų prioritetiškumą, naudingumo laipsnį bei rinkos vertę.Raktiniai žodžiai: nekilnojamojo turto agentų duomenų bazės, internetinė nekilnojamojo turto sprendimų paramos sistema, daugiakriterinis įvertinimasFirst Published Online: 14 Oct 2010